2020
DOI: 10.1021/acs.jpcb.0c06288
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Molecular Interactions in Liquid–Liquid Phase Separation of Disordered Proteins by Atomistic Simulations

Abstract: Membraneless organelles are dynamical cellular condensates formed via biomolecular liquid–liquid phase separation of proteins and RNA molecules. Multiple evidence suggests that in several cases disordered proteins are structural scaffolds that drive the condensation by forming a dynamic network of inter- and intramolecular contacts. Despite the blooming research activity in this field, the structural characterization of these entities is very limited, and we still do not understand how the phase behavior is en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
125
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(131 citation statements)
references
References 62 publications
6
125
0
Order By: Relevance
“…Overall, condensate immiscibility appears as a very general feature in biological systems, which could also be exploited to create synthetic membrane-less compartments [127,128]. Theoretical and computational studies on protein de-mixing [127,[129][130][131] confirm that protein phase diagrams are mainly shaped by salt concentration and solvent-mediated interactions, in turn influenced by temperature, their effects being cumulatively translated into "interfacial tension", i.e., the work required to increase the size of the interface between two adjacent, immiscible phases. [127].…”
Section: Phase Separation In Protein Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, condensate immiscibility appears as a very general feature in biological systems, which could also be exploited to create synthetic membrane-less compartments [127,128]. Theoretical and computational studies on protein de-mixing [127,[129][130][131] confirm that protein phase diagrams are mainly shaped by salt concentration and solvent-mediated interactions, in turn influenced by temperature, their effects being cumulatively translated into "interfacial tension", i.e., the work required to increase the size of the interface between two adjacent, immiscible phases. [127].…”
Section: Phase Separation In Protein Systemsmentioning
confidence: 99%
“…[127]. Sequence-specific properties, such as the presence of charged and aromatic residues, may then stabilize the de-mixing arrangements [130]. The role of salts on protein de-mixing has been considered for the peculiar case of multivalent ions [132,133].…”
Section: Phase Separation In Protein Systemsmentioning
confidence: 99%
“…In addition to overall net charge, recent theoretical and experimental work has demonstrated that the patterning of charged residues within disordered domains can fine-tune phase separation propensity (Lin et al, 2018;Nott et al, 2015;Pak et al, 2016;Paloni et al, 2020). We assessed the distribution of charged residues within the Cdt1 IDR by calculating the net charge per residue (NCPR) over a 5-residue window (Figure 2E, top).…”
Section: Proteinmentioning
confidence: 99%
“…Given the importance of chemical specificity of the sequence and also the importance of solvation, computer simulations with detailed atomic models with explicit solvent would be ideal to test and/or predict LLPS propensities of a given solution. However, the length and time scales are formidable and computationally intractable even for a simple model systems [33]. Coarse-grained (CG) models, with reduced representations of amino acids and solvents, provide a computationally tractable alternative.…”
Section: Introductionmentioning
confidence: 99%